Immune Checkpoint FGL1 Expression of Circulating Tumor Cells Is Associated With Poor Survival in Curatively Resected Hepatocellular Carcinoma - Yan, Qing; Lin, Hao-Ming; Zhu, Ke; Cao, Yi; Xu, Xiao-Lin; Zhou, Zi-Yu; Xu, Lei-bo; Liu, Chao; Zhang, Rui (Frontiers in Oncology, 2022)
FGL1 has been reported to be the main ligand of immune checkpoint LAG-3, and also plays a role in the inhibition of T cells. The role of FGL1 expression on circulating tumor cells (CTCs) and its clinical significance in hepatocellular carcinoma (HCC) remains unclear. Firstly, we performed the bioinformatics analysis to study the expression of FGL1 in various tumors and its effect on immune infiltration. After that, CTCs from 109 HCC patients were detected and the immunofluorescence staining was performed (CD45, EpCAM, CK8/18/19, Vimentin, Twist, DAPI and FGL1).Then, we investigated FGL1 expression and EMT of CTCs and analyzed its relationship with patient survival and clinical relevance. Bioinformatic results showed that FGL1 expression was abnormal in various tumor and it was correlated with the infiltration level of several immune cells. FGL1 expression was detected in CTCs of 40 patients (36.7%). The proportion of advanced TNM stage (P<0.001) and distant metastasis(P=0.020) in FGL1 positive patients was higher than that of FGL1 negative patients. In addition, patients with FGL1 positive circulating tumor cells had worse postoperative survival than FGL1 negative patients (p=0.0297). The FGL1 expression level of mixed phenotypic CTC was higher than other types of CTC, and the prognosis of patients with high number of mixed phenotypic CTC was also worse (p=0.0443). We also found that the expression of FGL1 on CTCs was associated with the level of FGL1 in tumor tissues. Among 109 patients, 12 patients received PD-1/PD-L1 immunotherapy and 10 of them was FGL1 positive and 8 patients were not responsive to immunotherapy. This is the first study demonstrating that FGL1 expression on CTCs was negatively correlated with the poor prognosis of HCC patients. CTC detection may serve as a replacement method for determination of tumor tissue FGL1 expression and provide evidence for the application of immunotherapy.